New stilbenes and phenolic constituents from the rhizomes of Belamcanda chinensis. Issue 10 (3rd October 2022) - Liu, Kai-Dong; Yang, Wan-Qi; Dai, Ming-Zhu; Sun, Shi-Kai; Fu, Jiang; Qu, Jing
Abstract: A pair of stilbenes with γ-lactam unit [(+)-1 and (−)-1 ], a new phenolic glucoside (2 ), and a new isoflavone glucoside (3 ), together with two known compounds (4-5 ) were isolated from the rhizomes of Belamcanda chinensis . The chemical structures of the undescribed compounds were elucidated on the basis of detailed spectroscopic analyses. Compounds 1, 4, and 5 (10 μM) exhibited anti-inflammatory activities with inhibition rates of 30.46%, 60.34%, and 37.91%, respectively, against the NF-κB signaling pathway. Abstract : UF0001